UNILATERAL PULMONARY ARTERY ATRESIA/AGENESIS: A CASE REPORT - Petre, Olvis; Irma, Tashi Bani; Jola, Hasani; Justi, Shestani; Silvana, Bala; Hasan, Hafizi (International Journal of Research -GRANTHAALAYAH, 2022)
A twenty-three-year-old male truck driver with a 12-pack year smoking history and no previous history of hospitalization was admitted to the “Shefqet Ndroqi” University Hospital pulmonology department after a cardiologist consultation where he was diagnosed with pulmonary hypertension. Two of the patient’s uncles from his mother’s side died during their pediatric age from congenital heart defects. A contrast-enhanced chest computed tomography was performed, and it showed an interruption of the lumen of the proximal part of the left pulmonary artery (atresia), a reduction of the left lung parenchyma volume, and bilateral pulmonary emphysema. The respiratory functional tests detected a moderate obstructive syndrome, and the 6MWT detected a decrease in arterial partial pressure of oxygen and oxygen saturation level. A diagnosis of unilateral pulmonary artery atresia/agenesis was confirmed.